The practice of using GPR technology in the examination tunnel - Kazarin, O. B.; Kazarin, B. O.; Husiev, D. Ye.; Pastushkov, H. P.; Pastushkov, V. H.; Zhykharev, D. V. (Science and Transport Progress, 2008)
In the paper the practical and analytical aspects of research methodology for a tunnel casings by georadar technologies are presented.